Stop the age clock - Lalvani, Vimla (Hamlyn, 2000)
Devised by revowned yoga teacher Vimla lalvani, 'Stop the Age Clock' is a collection of yoga workouts designed to combat the ageing process. It involves simple exercises which combine modern dance with classic yoga to help you look and feel younger in only 10 days. Concentrating on a different theme each day, the workouts tackle everything from toning the muscles, to dealing with stress through relaxation and meditiation.